2018
DOI: 10.1007/978-3-319-99498-7_20
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint/Rollback vs Causally-Consistent Reversibility

Abstract: This paper analyzes the relationship between a distributed checkpoint/rollback scheme based on causal logging, called Manetho, and a reversible concurrent model of computation, based on the π-calculus with imperative rollback developed by Lanese et al. in [?]. We show a rather tight relationship between rollback based on causal logging as performed in Manetho and the rollback algorithm underlying the calculus in [?]. Our main result is that the latter can faithfully simulate Manetho, where the notion of simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…A rollback is defined as the minimal causal-consistent sequence of backward steps able to undo a given action. The paper [69] explores the relationship between the Manetho [17] distributed checkpoint/rollback scheme (based on causal logging) and a reversible concurrent model of computation based on the π-calculus with imperative rollback called roll-π [38]. A rather tight relationship between rollback based on causal logging as performed in Manetho and the rollback algorithm underlying roll-π is shown.…”
Section: Recoverymentioning
confidence: 99%
“…A rollback is defined as the minimal causal-consistent sequence of backward steps able to undo a given action. The paper [69] explores the relationship between the Manetho [17] distributed checkpoint/rollback scheme (based on causal logging) and a reversible concurrent model of computation based on the π-calculus with imperative rollback called roll-π [38]. A rather tight relationship between rollback based on causal logging as performed in Manetho and the rollback algorithm underlying roll-π is shown.…”
Section: Recoverymentioning
confidence: 99%
“…This suggested that low energy consumption could be achieved by resorting to reversible computing, in which there is no information loss [3]. Nowadays, reversible computing has several applications ranging from modelling biochemical reactions [41,40] and parallel discrete-event simulation [38,43] to robotics [31], control theory [44], fault tolerant systems [9,11,24,46], and program debugging [13,28].…”
Section: Introductionmentioning
confidence: 99%
“…This notion of reversibility is natural in reliable distributed systems since when an error occurs the system tries to go back to a past consistent state. Examples of application of causal-consistent reversibility to model reliable systems include transactions [10,14] and rollback protocols [28]. Also, there are applications in program analysis and debugging [12,17].…”
Section: Introductionmentioning
confidence: 99%